Farmland Transaction Behavior Surveys and System Improvement Plans - 채광석 (농지거래 행태조사와 제도 개선 방안, 2015)
2014 marks 20 years since the legislation of the Farmland Act. Annual sales and purchase transactions of farmland in Korea exceed 3% of the total farmland, thus having higher mobilization level compared to other nations. Due to this, now over 50% of farmland became subject to leasing restrictions according to the Farmland Act after 20 years since the implementation of this law. However, it has not been supported by systems and organizations to efficiently manage this, and thus, the leased farmland ratio continued to increase and reached 50.0% in 2013, and there has also been an increase in farmland ownership by non-farmers. It is difficult for farmers to acquire farmland due to the land prices that are relatively higher than other countries. Identification of the actual state of farmland transactions (sales and leases) and changes in customary practices, and the provision of a feasible system in response to environmental changes have become more important than ever. For the reasonable use of farmland and system reforms, it is necessary to identify the reality of farmland transactions. The reason that surveys on farmland transactions are necessary is to go beyond simply knowing the level of farmland mobilization, but to accurately understand the decision-making process such as transaction purpose and behavioral features per subject in the course of farmland transactions. System improvement plans that reflect such behavioral features must be provided in order to draft good policies. The purpose of this study is to examine the behavior of farmland sales and lease transactions from the perspective of constructing a reasonable farmland usage system, and to present policy assignments to establish a farmland transaction order through this.